Hidden Power: Dynasty Politics in Konawe Regency? - Andi Muh. Dzul Fadli; Nartin; Sitti Rahmatyah; Jabal Arfah; Jefry Crisbiantoro; Milyan (Jurnal Administrasi Publik (Public Administration Journal), 2022)
In particular, this article aims to analyze several phenomena of hidden forms of power in the process of creating dynastic politics ahead of the 2024 concurrent municipal elections, a case study in the Konawe Regency. To do this, the author uses the Powercube-Gaventa theory from the perspective of hidden forms of power. The author uses a qualitative approach through interviews, observations, and document studies in the data collection process. This study provides several conclusions, including 1) There is alienation in PAN's internal candidacy process. Dynastic politics operates to control the other party and influence their decisions and support. Potential and experienced political party cadres are quickly eliminated; 2) Setting the agenda of the dynasty. Already exist at all levels of the legislature starting with the DPRD district, the DPRD and DPR RI provinces, and the regional bureaucracies; 3) Actual control of the party. There was a dynasty in the DPD PAN so an actor had a chance of being supported and promoted by the party. The results of this study are rather pragmatic, political parties do not create competent cadres, so they do not give birth to ideal figures through the influence of hidden power, especially in the local elections taking place at the same time in 2024. In addition, dynastic politics through party political instruments does not affect the existence of political waves and conflicts caused by the greater power of the regent (regional head) for the current dynasty-forming period.